PENGGUNAAN MODEL KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN PERKALIAN SISWA KELAS III SEKOLAH DASAR - Nur Fadilah; Asep Samsudin (STKIP Subang, 2022)
This study aims to demonstrate the effectiveness of using the make a match cooperative model to improve multiplication comprehension skills of third students of SD Muhammadiyah 2. This type of study is mixed methods with a sequential explanatory design. The sources obtained are quantitative data and qualitative data. Quantitative data collection techniques are used by conducting pretest-posttest, while qualitative data were obtained using student response questionnaires and observation sheets. Furthermore, the results of the N-gain score test, a score of 0,61 was obtained in the moderate category. Judging from the percentage of the effectiveness of the N-gain, a score of 56.22% was obtained with a fairly effective interpretation. Based o the research result, the researchers deduce that the model had improved the multiplication comprehension skills to third grade elementary school students is quite effective.